EFEKTIFITAS PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI TENGAH - Lestari, Dian Suci (Katalogis, 2018)
The research focused on the Effectiveness of Giving Additional Employee Income in Industry and Trade Office of Central Sulawesi Province. This study applied qualitative descriptive method with 7 informants selected on purpose. Theory applied was Gibson’s Effectiven ess theory consisted of some factors of effectiveness including Fulfilof Need, Attractiveness Closeness, Group’s Goal and Economic Reason. This research concluded that the Effectiveness of Giving Additional Employee Income in Industry and Trade Office of Central Sulawesi Province has not worked well. Satisfaction of Need has not been optimal. This was indicated by the assessment of work performance has not been in accordance with basic tasks and functions of works. The Additional Employee Income required responsibility. The Attractiveness Closeness has not been optimal caused by work assessment prioritized emotions, lack of work quality, also work quantity output and work time efficiency were still lacking. The Group’s Goal has not been optimal. In the Human Resource Assessment, the Additional Employee Income has not been based on workload and risk of work, it also happened with the discipline assessment which it was just for filling the attendance list not full time staying at the office.